Compatibility of antagonists with Azospirillum in sesamum - R. JEYARAJAN, P. SANKAR and (Indian Phytopathology, 2002)
A pot culture experiment was conducted to test the compatibility of antagonists, (Trichoderma, Gliocladium and Bacillus with Azospirillum) against root rot (caused by Macrophomina phaseolina) in a sesame crop. A combination of antagonists along with Azospirillum increased the root and shoot length of sesame significantly compared with Azospirillum alone. Reduced root rot and increased rhizosphere population were found in combined applications of antagonists. A combined application of all 3 antagonists resulted in the lowest root rot (13.3%) and increased shoot and root length. The rhizosphere population of Trichoderma and Gliocladium was reduced when applied with Bacillus subtilis.